2015
DOI: 10.1590/2176-9451.20.3.029-036.oar
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic evaluation of orthodontic treatment by means of four different cephalometric superimposition methods

Abstract: INTRODUCTION: Despite discussion on the merit of various cephalometric superimposition methods, there remains a need to assess which one can be used in daily practice with reasonably accuracy and less working time. OBJECTIVE: The aim of this study was to investigate four methods of cephalometric superimposition by means of assessing the longitudinal changes in craniofacial morphology caused by growth and response of adolescents with Class I malocclusion to orthodontic treatment involving first premolar extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 27 publications
0
11
2
1
Order By: Relevance
“…This is especially the case for historical studies such as this one, where radiographs from the 1950s‐80s are used that lack the clarity of more recent radiographs. Additionally, several different structural superimposition methods have been proposed with many studies reporting conflicting results about their relative strengths and weaknesses . Furthermore, some studies have demonstrated specific inaccuracies of superimposition methods, while other studies suggest the use of multiple superimposition methods for optimum results, which might be time‐consuming.…”
Section: Discussionmentioning
confidence: 99%
“…This is especially the case for historical studies such as this one, where radiographs from the 1950s‐80s are used that lack the clarity of more recent radiographs. Additionally, several different structural superimposition methods have been proposed with many studies reporting conflicting results about their relative strengths and weaknesses . Furthermore, some studies have demonstrated specific inaccuracies of superimposition methods, while other studies suggest the use of multiple superimposition methods for optimum results, which might be time‐consuming.…”
Section: Discussionmentioning
confidence: 99%
“…Superimposed tracing sefalometri radiograf pada pasien sebelum dan sesudah perawatan perlu dilakukan karena memiliki tingkat akurasi yang baik untuk menunjukkan perubahan posisi horisontal dan vertikal yang tepat, sehingga memungkinkan dokter gigi untuk melakukan penilaian keseluruhan dari efek yang terjadi karena pertumbuhan dan/ atau perawatan ortodontik. 15 Pasien dalam laporan kasus ini mengalami erupsi penuh pada gigi 13 impaksi dalam waktu 3 bulan setelah bedah open window dan kurang dari 1 bulan setelah perlekatan breket pada gigi tersebut.…”
Section: Laporan Kasusunclassified
“…0.3 ml in total was used in the region of the inferior lip (above the mentus) Fig. 19 Blue arrow indicates the ptosis area in the mandibular line, which should not be filled Lenza et al (2015) For the lips, the use of cannula or needles is possible, and the choice will depend on whether the aim is to volumize or contour (Fig. 20).…”
Section: Injection Techniquementioning
confidence: 99%